2019
DOI: 10.3390/app9030493
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Model for the Triple Phase Boundary of Solid Oxide Fuel Cell Electrospun Electrodes

Abstract: Electrospinning is a new state-of-the-art technology for the preparation of electrodes for solid oxide fuel cells (SOFC). Electrodes fabricated by this method have been proven to have an experimentally superior performance compared with traditional electrodes. However, the lack of a theoretic model for electrospun electrodes limits the understanding of their benefits and the optimization of their design. Based on the microstructure of electrospun electrodes and the percolation threshold, a theoretical model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…The optimization results showed that the optimal dimension values for the depth of the channel, the width of the channel, the width of the rib, and the transition radius were 0.5, 1.0, 1.6, and 0.5 mm, respectively, with the greatest reaction efficiency (79%) and acceptable formability (1.0). Kong developed a model capturing the key geometric parameters and their interrelationship, which were required to derive explicit expressions of the key electrode parameters in fuel cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…The optimization results showed that the optimal dimension values for the depth of the channel, the width of the channel, the width of the rib, and the transition radius were 0.5, 1.0, 1.6, and 0.5 mm, respectively, with the greatest reaction efficiency (79%) and acceptable formability (1.0). Kong developed a model capturing the key geometric parameters and their interrelationship, which were required to derive explicit expressions of the key electrode parameters in fuel cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the role of the diffusion layer of transferring reactants, the CCM plays a catalytic role in the water electrolysis. The concept of a three-phase boundary (TPB) exists in the water electrolysis reaction [ 24 , 25 , 26 ]. It is believed that in the water electrolysis reaction, the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) only occur in a limited-space area, which is at the junction of the PEM, the catalyst, and the pores of the diffusion layer.…”
Section: Methodsmentioning
confidence: 99%
“…Nanoparticle modified nanofibers have been successfully applied in divergent areas such as catalysis [1][2][3], tissue engineering [4], photochemical applications [5][6][7], capacitors [8], energy applications [9], membrane electrodes in fuel cells [10], etc... Fuel cells (FC) are environmentally friendly alternative power sources [11] and until now from solid oxide to microbial FCs various studies have been reported which use the advantage of electrospun polymers [10,[12][13][14][15]. Electrospun polymers exhibit unique electrochemical activity.…”
Section: Introductionmentioning
confidence: 99%